التنبؤ المالي كأداة لتحسين أداء الإدارة المالية بالمؤسسة الاقتصادية. دراسة حالة مؤسسة مطاحن سيدي أرغيس أم البواقي. - محمد كريم, قروف; سليم, العمراوي; هاني, علوي (Université de M'sila, 2020)
تهدف هذه الدراسة إلى إبراز أهمية تطبيق التنبؤ المالي كأداة لتحسين أداء الإدارة المالية بالمؤسسة الاقتصادية، وقد تم استخدام نموذج الانحدار الذاتي البسيط في التنبؤ بمبيعات منتوجات مؤسسة سيدي أرغيس بأم البواقي كدراسة تطبيقية للموضوع. ومن خلال التحليل الاحصائي لبيانات النماذج، كانت النتائج المتنبؤ بها في مجملها إيجابية، بحيث أنها تساهم في تحسين أداء الادارة المالية بالمؤسسة وتساعد في اتخاذ القرارات المناسبة لتحديد الأهداف المطلوبة سواء على المدى القصير أو المتوسط. Abstract : This study aims to demonstrate the importance of applying financial forecasting as a tool to improve the financial management performance of the economic institution. A simple self-regression model has been used to forecast sales of Sidi Argis Foundation products in Oum El Bouaghi as an applied study of the topic. Through statistical analysis of the model data, the predicted results in their entirety were positive, as they contribute to improving the performance of the financial management of the organization and help in taking appropriate decisions to determine the required goals, whether in the short or medium term.
Keywords: التنبؤ المالي ; الادارة المالية ; الاداء ; المؤسسة الاقتصادية